Novel thrombolytic agents for acute ischemic stroke: a comprehensive review of current evidence - Hotz, Julian; Kaindl, Lisa; Krebs, Stefan; Poli, Sven; Purrucker, Jan; Strbian, Daniel; Greisenegger, Stefan; Sykora, Marek (Journal of the neurological sciences, 2025)
Intravenous thrombolysis is one of the standard treatments of acute ischemic stroke. Over the last decades, alteplase (recombinant tissue type plasminogen activator, rt-PA) has been established as the main thrombolytic agent worldwide. However, the short plasma half-life of rt-PA poses logistical challenges, as it necessitates administration as a 10 % bolus followed by a 90 % infusion over one hour. These logistical difficulties, combined with the search for agents with improved efficacy and safety profiles, have spurred the development of alternative thrombolytic agents. This review summarizes current clinical evidence and emerging research on novel thrombolytic agents in acute ischemic stroke, including tenecteplase, reteplase, desmoteplase, urokinase, staphylokinase, JX10, LT3100, Ancrod, and TS23. Among these agents, tenecteplase has been most extensively studied and is already recommended for selected indications by the European Stroke Organization (ESO) and the American Heart Association and American Stroke Association (AHA/ASA). Other agents are still undergoing early clinical investigation and show different levels of potential in terms of effectiveness, safety, and ease of administration.